2004
DOI: 10.1109/tps.2004.835968
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Resonant Converter for Equilibrium and Nonequilibrium Plasma Discharges

Abstract: This paper proposes a new system to ignite and to sustain a plasma discharge for different reactor configurations, using a single-series parallel high-frequency resonant converter. The different operation modes are analyzed, and their performance is verified in two applications: an equilibrium plasma discharge (electric arc) and a nonequilibrium plasma discharge (electric barrier at atmospheric pressure) with intensity current and voltage amplitude varying from 135 mA and 1050 V to 600 mA and 502 V, and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The electric energy is provided by a high frequency resonant converter specially designed for this purpose (see figure 1(a)) [43]. The AC current can be adjusted from 10mA up to 2A peak to peak.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The electric energy is provided by a high frequency resonant converter specially designed for this purpose (see figure 1(a)) [43]. The AC current can be adjusted from 10mA up to 2A peak to peak.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The electrical energy is provided by a high-frequency resonant converter deeply described in [11], which is able to generate and sustain nonequilibrium and equilibrium plasma discharges. The data acquisition of the electrical voltage u(t) and current i(t) was carried out with a digital-scope Tektronix model THS710A.…”
Section: A Reactor and Equipmentmentioning
confidence: 99%
“…Our approach to the generation of glow-to-arc transitions has been through the use of a resonant converter as a highfrequency electrical source [11]. This converter has been tested in different reactor configurations and different plasma morphologies, and its universality has been demonstrated [12], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The power source consists on a high-frequency series resonant inverter working in the range 20-180 kHz and is able to generate a voltage of 15 kV [4]. The discharge is sustained at atmospheric pressure using nitrogen as plasma gas; it can be observed that the gliding discharge on the central electrode is reflected in the electrical signals [ Fig.…”
mentioning
confidence: 99%